Regular extension operators for partial fuzzy (pseudo)metrics - A. Savchenko (Математичні Студії, 2011)
Using the fuzzy modification of the Prokhorov metric on the set of probability measures we prove the theorem on existence of simultaneous extensions of partial fuzzy metrics (for the Lukasiewicz t-norm) defined on closed subsets of a compact metrizable space.